Banking secret in Peru: background, evolution, prospects and limits - Bueno Olazábal, Miguel (2024)
This article aims to give a general overview of the activity of the financial system from the perspective of passive operations, which are protected by a reinforced level of reserve, which is banking secrecy. The definition of the figure and its evolution in the recent economic field, its constitutional protection and the existing regulatory framework are analyzed, and then the exceptions, excluded information, prohibitions, cases of violation of banking secrecy, types of operations are reviewed. passives and their singularities are, to conclude on the current perspectives and challenges of the figure, raising some reflections as a conclusion.